Enhancing Community Empowerment with Digital Marketing for Social Forestry Enterprises in West Nusa Tenggara - Pawestri, Setyaning; Nofrida, Rini; Dewi, Endang Purnama; Fuadi, Mi’raj; Mustafid, M. Azhar; Antesty, Sella (Universitas Mataram, 2025)
The training on Strategi Peningkatan Pemasaran Produk KUPS melalui Digital Marketing was conducted at Hotel Aruna Senggigi, West Lombok Regency, on May 20, 2025, with the participation of social forestry groups (KUPS), forestry extension officers, and local stakeholders. The program aimed to strengthen the capacity of KUPS in adapting to digital markets. Participants gained a clearer understanding of the distinctions between selling, marketing, and branding, while also being introduced to current e-commerce trends in Indonesia, including Shopee, Tokopedia, and TikTok Shop. Qualitative evaluation revealed increased confidence, enthusiasm, and readiness to experiment with digital platforms, despite challenges such as limited internet access and digital literacy. The training demonstrated that digital marketing is not only a technical skill but also a pathway toward independence, competitiveness, and sustainability for social forestry enterprises.